Switchable Brillouin frequency multiwavelength and pulsed fiber laser - Tan, Sin Jin; Haris, Hazlihan; Harun, Sulaiman Wadi (Optical Society of America, 2017)
Switchable single and double Brillouin multiwavelength and pulsed laser is successfully demonstrated. Brillouin spacing can be switched from single (0.08 nm) to double spacing (0.16 nm) or vice versa by swapping the ports of the coupler in the proposed configuration. The proposed configuration can also be used to produce pulsed laser by inserting a home-made carbon nanotubes saturable absorber into the laser cavity. The proposed system is very versatile and flexible as it can be used as a multiwavelength laser or pulsed laser to cater for different types of applications.